Modeling Alzheimer’s disease brains in vitro - Henstridge, Christopher M.; Spires-Jones, Tara L. (Nature neuroscience, 2018)
Alzheimer’s disease (AD) research is hampered by a lack of models that recapitulate all key disease features. Park et al. introduce a microfluidic device containing a 3D culture of human neurons, astrocytes, and microglia that develop AD-like pathology, revealing a potentially important inflammatory mechanism of neurodegeneration.